Cholinergic hyperactivity in patients with myasthenia gravis with MuSK antibodies: A neurophysiological study. Issue 8 (August 2021) - Modoni, Anna; Mastrorosa, Alessia; Spagni, Gregorio; Evoli, Amelia
Highlights: Repetitive compound muscle action potential (R-CMAP) is a relatively common feature in MuSK-MG irrespective of AChE inhibitor treatment. This finding is more common in symptomatic patients and may result from a direct MuSK antibody effect. R-CMAP detection can represent a useful diagnostic clue for MuSK-MG and predicts poor tolerance to AChE inhibitors. Abstract: Objective: Patients with myasthenia gravis associated with muscle-specific tyrosine kinase antibodies (MuSK-MG) often manifest signs of cholinergic hyperactivity with standard doses of acetylcholinesterase inhibitors (AChE-Is). Aim of the study was to investigate whether repetitive compound muscle action potential (R-CMAP), the neurophysiological correlate of cholinergic hyperactivity, was present in MuSK-MG irrespective of AChE-I treatment. Methods: Patients with confirmed diagnosis of MuSK-MG were consecutively enrolled during follow-up visits, from January 2019 to April 2020. All these subjects underwent the same neurophysiological protocol, including motor nerve conduction studies and repetitive nerve stimulation. In patients taking pyridostigmine, neurophysiological testing was performed at least 12 hours after the last dose. For comparison, the presence of R-CMAP was investigated in 20 consecutive acetylcholine receptor antibody positive myasthenia gravis (AChR-MG) patients. Results: We enrolled 25 MuSK-MG patients (20 females), aged 16–79 years at the study time, with disease duration ranging 0.6–48.8 years (median: 17.7 years). R-CMAP was detected in 12/25 (48%) MuSK-MG cases and in none of the AChR-MG controls (p = 0.0003). In the MuSK-MG population, a history of muscle cramps and fasciculations, during low-dose pyridostigmine therapy, was significantly more frequent in R-CMAP positive than in R-CMAP negative patients (100% vs 31%, p = 0.001). At the time of the study, the proportion of patients still symptomatic for MG was higher among R-CMAP positive cases (92% vs 23%, p = 0.0005). Conclusions: Cholinergic hyperactivity is a relatively common finding in MuSK-MG patients, independent of AChE-I treatment, and may constitute an intrinsic feature of the disease. Significance: R-CMAP detection can represent a useful diagnostic clue for MuSK-MG and predicts poor tolerance to AChE-Is.